Authigenic Formation of Clay Minerals in the Abyssal North Pacific. Issue 11 (10th November 2022) - Steiner, Zvi; Rae, James W. B.; Berelson, William M.; Adkins, Jess F.; Hou, Yi; Dong, Sijia; Lampronti, Giulio I.; Liu, Xuewu; Achterberg, Eric P.; Subhas, Adam V.; Turchyn, Alexandra V.
Abstract: Present estimates of the biogeochemical cycles of calcium, strontium, and potassium in the ocean reveal large imbalances between known input and output fluxes. Using pore fluid, incubation, and solid sediment data from North Pacific multi‐corer cores we show that, contrary to the common paradigm, the top centimeters of abyssal sediments can be an active site of authigenic precipitation of clay minerals. In this region, clay authigenesis is the dominant sink for potassium and strontium and consumes nearly all calcium released from benthic dissolution of calcium carbonates. These observations support the idea that clay authigenesis occurring over broad regions of the world ocean may be a major buffer for ocean chemistry on the time scale of the ocean overturning circulation, and key to the long‐term stability of Earth's climate. Key Points: North Pacific red clay sediments are a sink for marine calcium, strontium, and potassium Authigenic formation of clay minerals is prevalent in pelagic sediments throughout the North Pacific The main mechanism for clay formation is recrystallization of aluminosilicates, neoformation can occur in biogenic silica rich sediments